Regulating European telecommunications markets: Unbundled access to the local loop outside urban areas - Anne Gabelmann (Albert-Ludwigs-Universität Freiburg, Institut für Verkehrswissenschaft und Regionalpolitik, 2001)
This paper examines the topic of unbundled access to the local loop in areas which show characteristics of non-contestable natural monopolies outside the large cities. Under the heading "local loop unbundling" three variants are discussed, full unbundling, line sharing, and bitstream access. An obligation to provide competitors access to local networks on an unbundled basis is a strong intervention into the property rights of the regulated firm. In this light the following points particularly come into question: Who should be granted the right to access local loops on an unbundled basis? Which form(s) of local loop unbundling should be enforced?
Keywords: 330; Fixed Line Communications; Network Access; Local Loop Unbundling; Telekommunikation; Gemeinde; Netzzugang; Telekommunikationspolitik; Wettbewerb; Natürliches Monopol; EU-Staaten